High Peptide Dose Vaccination Promotes the Early Selection of Tumor Antigen-Specific CD8 T-Cells of Enhanced Functional Competence - Carretero-Iglesia, Laura; Couturaud, Barbara; Baumgaertner, Petra; Schmidt, Julien; Maby-El Hajjami, Hélène; Speiser, Daniel E.; Hebeisen, Michael; Rufer, Nathalie (Frontiers in Immunology, 2020)
CD8 T-cell response efficiency critically depends on the TCR binding strength to peptide-MHC, i.e. the TCR binding avidity. A current challenge in onco-immunology lies in the evaluation of vaccine protocols selecting for tumor-specific T-cells of highest avidity, offering maximal immune protection against tumor cells and clinical benefit. Here, we investigated the impact of peptide and CpG/adjuvant doses on the quality of vaccine-induced CD8 T-cells in relation to binding avidity and functional responses in treated melanoma patients. Using TCR-pMHC binding avidity measurements combined to phenotype and functional assays, we performed a comprehensive study on representative tumor antigen-specific CD8 T-cell clones (n = 454) from seven patients vaccinated with different doses of Melan-A/ELA peptide (0.1 mg versus 0.5 mg) and CpG-B adjuvant (1-1.3 mg versus 2.6 mg). Vaccination with high peptide dose favored the early and strong in vivo expansion and differentiation of Melan-A-specific CD8 T-cells. Consistently, T-cell clones generated from those patients showed increased TCR binding avidity (i.e. slow off-rates and CD8 binding independency) readily after 4 monthly vaccine injections (4v). In contrast, the use of low peptide or high CpG-B doses required 8 monthly vaccine injections (8v) for the enrichment of anti-tumor T-cells with high TCR binding avidity and low CD8 binding dependency. Importantly, the CD8 binding-independent vaccine-induced CD8 T-cells displayed enhanced functional avidity, reaching a plateau of maximal function. Thus, T-cell functional potency following peptide/CpG/IFA vaccination may not be further improved beyond a certain TCR binding avidity limit. Our results also indicate that while high peptide dose vaccination induced the early selection of Melan-A-specific CD8 T-cells of increased functional competence, continued serial vaccinations also promoted such high-avidity T-cells. Overall, the systematic assessment of T-cell binding avidity may contribute to optimize vaccine design for improving clinical efficacy.